Effect of regorafenib in delaying definitive deterioration in health-related quality of life in patients with advanced cancer of three different tumor types - Hofheinz, Ralf-Dieter; Bruix, Jordi; Demetri, George D.; Grothey, Axel; Marian, Marisca; Bartsch, Jennifer; Odom, Dawn (Cancer management and research, 2021)
The objective of this post hoc exploratory analysis was to explore the impact of regorafenib on delaying HRQOL deterioration across three different tumor types.
Gesehen am 17.01.2023